A Study on Attention Attracting Elements of 360-Degree Videos Based on VR Eye-Tracking System - Choi, Haram; Nam, Sanghun (Multimodal technologies and interaction, 2022)
In 360-degree virtual reality (VR) videos, users possess increased freedom in terms of gaze movement. As a result, the users’ attention may not move according to the narrative intended by the director and miss out on important parts of the narrative of the 360-degree video. Therefore, it is necessary to study a directing technique that can attract user attention in 360-degree VR videos. In this study, we analyzed the directing elements that can attract users’ attention in a 360-degree VR video and developed a 360 VR eye-tracking system to investigate the effect of the attention-attracting elements on the user. Elements that can attract user attention were classified into five categories: object movement, hand gesture, GUI insertion, camera movement, and gaze angle variation. We developed a 360 VR eye-tracking system to analyze whether five attention-attracting elements influence the user’s attention. Based on the eye tracking system, an experiment was conducted to analyze whether the user’s attention moves according to the five attention-attracting elements. Based on the experimental results, it can be seen that ‘hand gesture’ attracted the second most attention shift of the subjects, and ‘GUI insertion’ induced the smallest shift of attention of the subjects.